Haiti, history, and the gods - Dayan, Colin (University of California Press, 1995)
In 'Haiti, History, and the Gods', Joan Dayan charts the cultural imagination of Haiti not only by reconstructing the island's history but by highlighting ambiguities and complexities that have been ignored. She investigates the confrontational space in which Haiti is created and recreated in fiction and fact, text and ritual, discourse and practice.
Reprint. Originally published: Berkeley : University of California Press, 1995.
"A centennial book."
Keywords: Haiti -- Civilization -- Philosophy.; Haiti -- Religion.; Nationalism -- Haiti -- Religious aspects.; Social psychology and literature -- Haiti -- History.; Nationalisme -- Haïti -- Aspect religieux.; Psychologie sociale et littérature -- Haïti -- Histoire.; HISTORY -- General.; HISTORY -- Latin America -- General.; Civilization -- Philosophy; Nationalism -- Religious aspects; Religion; Social psychology and literature; Haiti; History